Little dimension and the improved new intersection theorem - Nakamura, Tsutomu; Takahashi, Ryo; Yassemi, Siamak (Mathematica Scandinavica, 2020)
Let $R$ be a commutative noetherian local ring. We define a new invariant for $R$-modules which we call the little dimension. Using it, we extend the improved new intersection theorem.